Assessing the effective marketing and employers' perception of the quality of the Diploma In Public Administration at UiTM Sarawak Branch / Kuldip Singh, Prabha Ramakrishnan and Elizabeth Caroline Augustine (Universiti Teknologi MARA, Sarawak, 2005)
This study examines the socio-economic status and employers' perceptions of the work quality of Diploma Public Administration (DPA) graduates from the Universiti Teknologi Mara (UiTM) Sarawak Branch who graduated between 1997 and 2000. In addition, the study also examines graduate perceptions of the relevance of the DPA program to employability. Our sample consisted of 436 graduates. The response rate for graduates was 36 percent and the employers' response was 17 percent. The study shows that the profile of a typical DPA graduate is below 30 years old, earning less than RM1, 500 per month, has Cumulative Grade Point Average (CGPA) of 2.80 and is employed in the Government sector. Our findings indicate that 70 percent of DPA graduates are employed and 14 percent are pursuing higher education. Regarding the DPA curriculum structure, the majority of respondents are of the opinion that it is relevant to the job market however more emphasis needs to be given to improving the standard of English language amongst DPA graduates. There were requests for extended industrial attachments, the teaching of communication skills and Information Communication Technology (ICT) skills. Employers are of the opinion that UiTM DPA graduates exhibit similar work quality to other local university graduates. DPA graduates also scored well in the generic skills required by employers.